Offshore territories: basic concepts of functioning - Kleshcheeva, M.V. (Економічний вісник Донбасу, 2010)
In this article the author tries to bring the most vivid examples of the functioning of offshore zones (Problems and Prospects) and their impact on national economies as a whole. Study of the special status of offshore zones and modalities for a solution to the problems associated with the implementation of shadow operations in these centers. Key words: Offshore, offshore centers, globalization, growth, factors, influential, theory, foreign investments. У статті автор намагається привести найбільш яскраві приклади функціонування оффшорних зон (проблеми та перспективи) та їх вплив на економіку країн у цілому. Вивчення особливого статусу офшорних зон та умов їх функціонування може бути розв’язанням проблем пов’язаних зі здійсненням тіньових операцій у цих центрах. Ключові слова: Офшори, офшорні центри, глобалізація, економічне зростання, фактори, впливовість, теорія, іноземні інвестиції. В этой статье автор старается привести наиболее яркие примеры функционирования оффшорных зон (проблемы и перспективы) и их влияние на экономику стран в целом. Изучение особого статуса оффшорных зон и условий их функционирования служит решением проблем связанных с осуществлением теневых операций в этих центрах. Ключевые слова: Оффшоры, оффшорные центры, глобализация, экономический рост, факторы, влиятельность, теория, иностранные инвестиции.